Predictors of length of career sfter hip arthroscopy for femoroacetabular impingement in professional hockey players - Menge, T. J.; Briggs, K.; Pilippon, M. J. (The American Journal of Sports Medicine, 2016)
Background: Previous studies have shown that professional hockey players return to sport at a high rate after hip arthroscopy, although it is unknown how long players continue to compete at a professional level after surgery. Purpose: To determine the prevalence of athletes who continued playing in the National Hockey League (NHL) for a minimum of 5 years after hip arthroscopy for treatment of symptomatic femoroacetabular impingement (FAI) and to determine predictors associated with length of career. Study Design: Case series; Level of evidence, 4. Methods: A total of 60 professional hockey players (69 hips) underwent hip arthroscopy for FAI by a single surgeon between 2005 and 2010. Data were retrieved from NHL.com and Hockey-reference.com regarding information on each player`s professional career. Position played, age, surgical procedure, and intraoperative findings were also used in data analysis. Results: There were 12 centers, 15 defensemen, 16 goalies, and 17 wings studied. Of the 60 athletes, 40 (67%) continued to play professionally a minimum of 5 years after hip arthroscopy. As of the 2015 season, the mean length of a player`s NHL career was 13.7 years (range, 2-27 years), with an average of 5.9 years played after hip arthroscopy. There was no difference in length of career or years played when goalies were compared with other positions (P = .760). Length of career and years played after arthroscopy correlated with age at surgery (r = 0.799 and -0.408, respectively). Players who played =5 years after arthroscopy were significantly younger than those who did not (25 vs 30 years; P = .001). Athletes who played <5 years after arthroscopy had a longer average duration of symptoms before surgery when compared with those who played =5 years (20.2 vs 9.3 months; P = .049). There were no differences in length of career or years played after arthroscopy based on type of labral treatment. Conclusion: Professional NHL players who underwent hip arthroscopy for FAI were able to continue playing for an average of 5.9 years after surgery, with 67% playing a minimum of 5 years postoperatively. Younger age and shorter duration of symptoms at time of surgery correlated with greater length of career and years played after hip arthroscopy. Players who did not play a minimum of 5 years postoperatively had significantly longer duration of symptoms before surgery. The study data support early arthroscopic treatment of professional hockey players with symptomatic FAI.